2020
DOI: 10.1534/g3.120.401269
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Accumulation of Nonsynonymous Mutations and Favorable Pleiotropic Alleles During Wheat Breeding

Abstract: Plant breeding leads to the genetic improvement of target traits by selecting a small number of genotypes from among typically large numbers of candidate genotypes after careful evaluation. In this study, we first investigated how mutations at conserved nucleotide sites normally viewed as deleterious, such as nonsynonymous sites, accumulated in a wheat, Triticum aestivum, breeding lineage. By comparing a 150 year old ancestral and modern cultivar, we found recent nucleotide polymorphisms altered amino acids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…This exhibits Rht-D1 as a major gene conveying a negatively pleiotropic effect on FHB resistance. As indicated by Raherison et al ( 2020 ), alleles of negatively pleiotropic loci exert favourable effects on one trait and unfavourable effects on the other trait depending on the breeding objectives. In commercial wheat breeding, the reduction effect of Rht-D1b on plant height represents a favourable effect, while its increase effect on FHB severity or susceptibility is perceived as an unfavourable effect.…”
Section: Discussionmentioning
confidence: 98%
“…This exhibits Rht-D1 as a major gene conveying a negatively pleiotropic effect on FHB resistance. As indicated by Raherison et al ( 2020 ), alleles of negatively pleiotropic loci exert favourable effects on one trait and unfavourable effects on the other trait depending on the breeding objectives. In commercial wheat breeding, the reduction effect of Rht-D1b on plant height represents a favourable effect, while its increase effect on FHB severity or susceptibility is perceived as an unfavourable effect.…”
Section: Discussionmentioning
confidence: 98%
“…Current entries could harbor relatively beneficial allele combinations whose inheritance stably contributes to positive, progeny values (Fradgley et al., 2019), but these long haplotypes certainly make suboptimal trait contributions. Nonsynonymous mutations accumulate during wheat breeding (Raherison et al., 2020), and the mutations may preferentially accumulate in these pericentromeric regions. Recombination could generate phenotypic diversity and reduce genetic load by decoupling linked deleterious alleles and beneficial variants (Rodgers‐Melnick et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Trade-offs between grain yield and both protein content and weed competitive ability seem not to have been generally addressed by commercial breeding due to yield being considered the highest economically important trait. Recent analysis by Raherison et al (2020) suggested that negative pleiotropic genetic effects in wheat have rarely been compensated for and optimised by breeding, and Yang et al (2022) showed that breeders’ selections have almost always been in favour of yield at the expense of protein. Changing economic, legislational, environmental and societal factors mean that breeding focus will increasingly need to consider how to deliver sustainable intensification of food supply, ensuring yield stability of our future crops in the face of such pressures.…”
Section: Introductionmentioning
confidence: 99%